Analysis on MTGase catalysed cross-linked products of Ara h 2: structure and immunoreactivity. Issue 1 (1st January 2018) - Chang, Xuejiao; Wu, Zhihua; Zhao, Ruifang; Zhang, Ying; Li, Xin; Yang, Anshu; Tong, Ping; Chen, Hongbing
ABSTRACT: Peanut is ranked among the eight major food allergens. Ara h 2 is its major allergen, recognized by more than 90% of serum IgE from peanut-allergic patients. Cross-linking catalysed by microbial transglutaminase (MTGase) is proved to be feasible to decrease the allergenicity of Ara h 2. The crosslinking reaction occurred both inter- and intra-molecular could gain products with different molecular weights. In this study, after MTGase catalysed crosslinking, the products were separated into low molecular weight part of Ara h 2 (LP-Ara h 2) and high molecular weight part of Ara h 2 (HP-Ara h 2), and the structure, digestibility, IgG and IgE binding capability of each part were analysed. Compared with LP-Ara h 2, HP-Ara h 2 was found to have looser structure, higher digestion rate and corresponding lower immunogenicity. By controlling the reaction condition to get different products, the protein desensitization processes would get a better result.